The Citizen School: Inclusive policies and practices - Azevedo, Jose Clovis de; Rodrigues, Carolina Contreiras; Curço, Sumaia Fuchs (Education Policy Analysis Archives, 2010)
The experience of Porto Alegre Citizen school is discussed in this study, being analyzed how this democratic participation based project has produced advances in the educational inclusion issue. The Citizen School project is discussed in the context of conquests and advances within the Brazilian legislation. Education is discussed as a right, which analyses the contradictions of the inclusion process limited by the excludent socioeconomical system. The assumptions and the pedagogical practises which produce the schooling failure are examined by presenting a critical view towards the merit conception-based evaluation. It is discussed the need of rethinking school centering the concerns with inclusion and educators training intended to gather the “different ones” and allow dialogues with the cultural contexts. The ongoing project at the Citizen School is being analyzed as an updated pedagogical practice reference. The data examined is referred to the Municipal net and indicates a rise in enrollments, in the different modalities of attending, in evasion reduction, in failing and shows a drastic decrease of illiteracy in the city. It also testifies a continuance of an integrating, cooperative, solidary, participative and democratic pedagogical practice commited to social inclusion.